Eksplorasi Etnomatematika Pada Budaya Pesantren Terhadap Bentuk Geometri Desain Auditorium Di Pondok Pesantren Baitul Arqom Balung - Devi, Rahayu Sandra; Panglipur, Indah Rahayu; Hidayatin, Nur (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
Auditorium Pesantren Baitul Arqom Balung is one of the cottage buildings that is quite interesting to research. This research uses qualitative research with an entographic approach design. The purpose of this research is to describe the ethnomathematics study of the Auditorium building to explore information about the concept of geometry in the building. The data in this study were obtained from observation and documentation. The results of the study are the relationship between the mathematical concept of introducing geometric shapes in the Auditorium building of the Baitul Arqom Balung Islamic Boarding School. In the study of ethnomathematics exploration on the shape of the Auditorium building, there is a form of geomtery which is part of mathematics material, namely the geometry of flat shapes, namely kites, equilateral triangles, isosceles trapezoids, circles, hexagons and rhombuses. The concept of wake transformation is used in the arrangement of ornaments. therefore, the Auditorium of Baitul Arqom Balung Islamic Boarding School can be used as a source of learning and insight into the concept of geomtery.